Review of indices evaluating potential phosphorus release from sediments in lakes and reservoirs -- history, approaches, advantages, and limitations - Wen Zhang; Junxi Yang; Yuepeng Yin; Anqi Guo; Tongtong Rao; Peng Wang; Qiang Xu (Ecological Indicators, 2025)
Evaluating potential phosphorus (P) release from sediments is critical for controlling lakes and reservoirs eutrophication. This review summarized history, procedures, and particular purposes of 15 existing indices into 5 groups covering studies conducted globally from 1950 to 2024, and discussed their advantages and limitations, which has never been systematically elaborated upon before. We concluded that Sediment Test P (STP) indices, using chemical extractions (e.g., acids, bases, salts), effectively estimate bioavailable P (BAP). P Homeostasis Indices (PHI), derived from sorption isotherm modeling (e.g., Langmuir/Freundlich), predict P release potential (e.g., EPC0) and maximum sorption capacity (Qmax), though humic-rich DOM can interfere. Potential Available P (PAP) indices, based on sequential fractionation (targeting loosely-bound, Fe/Mn/Al-P), correlate strongly with BAP and mobile P, aiding risk assessment. P Saturation Evaluation (PSE) indices, calculated as ratios (e.g., oxalate-P/(Fe + Al)), identify P retention thresholds but require cross-validation for heterogeneous sediments. Emerging P Storage Capacity (PSC) indices, quantifying remaining binding capacity, assess legacy P but are currently limited to streams. Moreover, using fresh or freeze-dried sieved sediment samples enhances representativeness over drying sediments. While these indices enhance P management, combining multiple indices and conducting kinetics of P release simulation experiment with intact core incubations under controlled pH/Eh conditions are recommended for precise flux quantification. This systematic comparison highlights methodological strengths (e.g., STP practicality, PSE predictive utility) and limitations (e.g., PHI sensitivity to organic interference, PSC narrow applicability), offering guidance for selecting context-appropriate tools. Our findings inform watershed policies targeting P load reduction and underscore the need for further validation to optimize index performance in achieving ecological objectives.